Identification of Quina and Vasconian technocomplexes in Gatzarria Cave (north-western Pyrenees), based on the stratigraphic, taphonomic and technological revision of the Georges Laplace collections - Deschamps, Marianne (2019)
The archaeo-sequence of Gatzarria Cave (Ossas-Suhare, Pyrénées-Atlantiques, France), in the northwestern foothills of the Pyrenees, records several phases of the Middle Palaeolithic and the initial stages of the Upper Palaeolithic. This type of deposit in a karstic context enables us to characterize diachronic changes in industries and to demonstrate the relative preservation of the assemblages. This cavity was excavated by Georges Laplace between 1951 and 1976 and contains a complex stratigraphy that was exposed to significant post-depositional processes. It was thus essential to test that the archaeological levels were intact before any techno-economic analysis. Several recent studies have questioned the homogeneity of the archaeological remains in the back of the cave. This article focuses on the sequencing of the industries attributed to the Quina and the Vasconian, based on the correlation of different types of taphonomic and typo-technological analyses (density of remains, surface conditions, refits, spatial distribution, analysis of the fieldwork notebooks). Ultimately, this work sheds light on the sequencing of lithic technocomplexes at a macro-regional scale in a relatively poorly-documented key zone between northern Aquitaine and the Cantabrian mountains.